SOIL CONSERVATION TECHNIQUES IN OIL PALM CULTIVATION FOR SUSTAINABLE AGRICULTURE - Halus Satriawan; Zahrul Fuady; Agusni Agusni (Graduate School Bogor Agricultural University (SPs IPB), 2017)
Currently, many have been concerned with the oil palm cultivation since it may also put land resources in danger and bring about environmental damage. Poor practices in managing agricultural land very often occur due to the inadequate knowledge of soil conservation. Application of soil and water conservation is to maintain the productivity of the land and to prevent further damage by considering land capability classes. This research was aimed at obtaining soil and water conservation techniques which are the most appropriate and optimal for oil palm cultivation areas based on land capability classes which can support sustainable oil palm cultivation. Several soil conservation techniques had been treated to each different class III, IV, and VI of the studied area. These treatment had been performed by a standard plot erosion. The results showed for the land capability class III, Cover plants + Manure was able to control runoff, erosion and reduce leaching of N (LSD P≤0,05), in which soil conservation produced the lowest erosion (3,73t/ha), and N leaching (0,25%). On land capability class IV, Sediment Trap + cover plants+ manure was able to control runoff, erosion and reduce organic C and P leaching (LSD P≤0,05), in which soil conservation produced the lowest runoff (127,77 m3/ha), erosion (12,38t/ha), organic C leaching (1,14 %), and P leaching (1,28 ppm). On land capability class VI, there isn’t significant effect of soil conservation, but Bench Terrace + cover plants +manure has the lowest runoff, erosion and soil nutrient leaching.